2017
DOI: 10.1016/j.jclepro.2016.12.125
|View full text |Cite
|
Sign up to set email alerts
|

Natural evolution of alkaline characteristics in bauxite residue

Abstract: Bauxite residue, a highly alkaline solid waste, is extremely hazardous to the surrounding environment and current research approaches have largely focused on the removal and separation of alkaline substances. Natural weathering processes may be a step forward in terms of their regeneration. In this study, natural evolution of basic alkalinity, electrical conductivity, exchangeable ions and acid neutralizing capacity of residue in the disposal areas is discussed. Minerals, exchangeable cations and alkaline anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 124 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Similarly, Courtney et al (2013) found that the bauxite tailings remained strongly alkaline and saline over a long-term storage period without amendments. However, Kong et al (2017) found that the alkalinity and salinity decreased during the long-term natural aging (5-20 years). These differences may because of mineralogical and geochemical differences and local climatic conditions (such as temperature and water supply).…”
Section: Slow Changes Of Physico-chemical Characteristics In the Tailmentioning
confidence: 99%
“…Similarly, Courtney et al (2013) found that the bauxite tailings remained strongly alkaline and saline over a long-term storage period without amendments. However, Kong et al (2017) found that the alkalinity and salinity decreased during the long-term natural aging (5-20 years). These differences may because of mineralogical and geochemical differences and local climatic conditions (such as temperature and water supply).…”
Section: Slow Changes Of Physico-chemical Characteristics In the Tailmentioning
confidence: 99%
“…Following natural processes, sodalite, hydrogarnet, and calcite decreased, as did pH. Reduction of pH resulted in the precipitation of Ca(OH) 2 but also leaching of NaOH by exchange reactions as the charged colloid (such as Al(OH) 6 3− ) was a regulator for cation exchange (Kong, Guo, et al, ). As a result, ESP decreased.…”
Section: Resultsmentioning
confidence: 99%
“…WDC, which was used to estimate microaggregate instability, ranged ) was a regulator for cation exchange (Kong, Guo, et al, 2017). As a result, ESP decreased.…”
Section: Microaggregate Stability Of the Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation is critical to stabilize the mined and mine waste land, to reduce long‐term environmental pollution, and to minimize ecological impacts (Goloran et al, ; Wong, ). This is particularly the case for bauxite processing residue (bauxite residue or red mud, a high alkaline solid waste) from alumina extraction (Gelencser et al, ; Kong, Guo, et al, ; Mayes et al, ), which can produce approximately 0.5–2 tons of residue generated per ton of alumina product (Evans, ; Grafe, Power, & Klauber, ). Currently, the accumulative inventory of bauxite residue has reached over 4 billion tons and is still increasing rapidly (Kinnarinen, Holliday, & HĂ€kkinen, ; Liu & Naidu, ; Ye et al, ).…”
Section: Introductionmentioning
confidence: 99%